A simple solution-phase approach to synthesize high quality ternary AgInSe2 and band gap tunable quaternary AgIn(S1−xSex)2 nanocrystals - Bai, Tianyu; Li, Chunguang; Li, Feifei; Zhao, Lan; Wang, Zhaorui; Huang, He; Chen, Cailing; Han, Yu; Shi, Zhan; Feng, Shouhua (Nanoscale, 2014)
A facile solution-phase route for the preparation of AgInSe2 nanocrystals was developed by using silver nitrate, indium stearate, and oleylamine-selenium (OAm-Se) as precursors. The evolution process of the AgInSe2 nanocrystals is discussed in detail and different reaction conditions all have a great impact on the growth and morphology of the nanocrystals. Alloyed AgIn(S1-xSex)2 nanocrystals with controlled composition across the entire range (0 ≤ x ≤ 1) was also successfully prepared by modulating the S/Se reactant mole ratio. X-ray diffraction (XRD), energy dispersive X-ray (EDX), X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy (TEM) were used to confirm that the alloyed AgIn(S1-xSex)2 nanocrystals are homogeneous. The UV-vis absorption spectra revealed that the band gap energies of the alloyed AgIn(S1-xSex)2 nanocrystals could be continuously tuned by increasing the Se content.